Diselenide-based nanoparticles enhancing the radioprotection to the small intestine of mice - Yichi Huang; Jiaze Li; Sen Wang; Hongqi Tian; Saijun Fan; Yu Zhao (Journal of Nanobiotechnology)
Abstract The widespread application of ionizing radiation (IR) in medicine, while beneficial, also poses potential risks that necessitate effective countermeasures. Both 2-(3-aminopropylamino) ethanethiol (WR-1065) and curcumin are recognized as radioprotective agents; however, their clinical utility is hindered by notable shortcomings that could be addressed through reactive oxygen species (ROS)-responsive amphiphilic nanomaterials. We introduced a newly synthesized poly (ethylene glycol) (PEG)-polycaprolactone (PCL) polymer integrated with diselenide bonds and curcumin (HOOC-SeSe-Cur-PEG-SeSe-Cur-PCL, PEG-Cur-SeSe-PCL). The resulting spherical nanoparticles (NPs), which self-assembled from this polymer, were uniform with an average diameter of 118 nm. As a carrier for WR-1065, these NPs demonstrated a loading capacity of 30.9% and an efficacy of 56.7%. Importantly, the degradation of WR-1065 within the NPs was minimal in gastric fluid, decreasing by only approximately 20% over a 6-hour period. The innovative aspect of these NPs is their design to destabilize in ROS-rich environments, facilitating the release of WR-1065 and curcumin. Indeed, the survival rate of mice increased to 50% when these NPs were orally administered prior to exposure to a lethal dose of whole-body irradiation (8 Gy). The radioprotective impact of WR-1065-loaded NPs was evident in the small intestine of irradiated mice, characterized by the amelioration of radiation-induced epithelial damage, reduction of DNA damage, and inhibition of the apoptotic pathway. Collectively, this oral nanocarrier system for WR-1065 and curcumin holds promise as a potential candidate for the prophylaxis and treatment of acute intestinal injuries induced by IR. Graphical Abstract